MELACAK HUBUNGAN KESULTANAN SAMBAS DAN BUGIS (Studi Awal terhadap Naskah Tuhfat al-Nafis) - Sunandar Sunandar (The Pontianak State Institute of Islamic Studies, 2014)
This article discusses about the relationship of the Sultanate of Sambas and Bugis through script Tuhfat al-Nafis. The study of Malay manuscripts which have historical value would be useful in the study of Malay historiography. In TN has been providing information about the relationship between the Sultanate of Sambas and Bugis through marriage between Daeng Kemase and sister of Sultan Umar Aqamaddin I named Raden Tengah. Relationships that are woven through the marriage give influence to the development of Islam in Sambas, which with the arrival of Shaykh Abdul al-Jalil al-Fatani from Patani in Southern Thailand.